Art Therapy in Eliminating Aggressiveness in the Individual - Yuldashev Tojiddin Abdukarimovich; Shomurodov Ulug'bek Melikmurodovich (Global Scientific Publishing, 2022)
The process of working with the parents of an angry child is challenging. The main cause of this is that those parents had aggressive behavior when they were young. Additionally, their offspring will "inherited" mental health issues. As a result, the psychologist should engage in as much psychotherapeutic work with parents as possible. Parents view violent kids as ungrateful and anticipate that the child will feel guilty after arguing with them and regretting it, apologizing and calming them down. This article will provide feedback and input on art therapy in the removal of aggressiveness in the individual.
Keywords: aggressiveness; personality; art Therapy; elimination